Evaluation Of The Quality Of Packed Red Cell (PRC) In the Blood Donation Unit (BDU) Of The Indonesian Red Cross (IRC) Of Banda Aceh City: Haemolysis Rate As An Indicator Of A Good Quality Control Process - Teuku Ilhami Surya Akbar; Wizar Putri Mellaratna; Ratna Sari Dewi; Evanulia Evanulia (Buletin Farmatera, 2023)
Abstract: PRC is the most commonly used component of blood. This blood component comes from whole blood which then goes through a centrifugation process to separate into PRC blood components. In this separation process, it is not uncommon to cause haemolysis, which in the end PRC blood products do not provide a therapeutic effect for recipients. This study will look at the percentage of haemolysis that occurs during separation and whether it is still up to standard. This study aims to determine the risk of haemolysis in the processing of PRC blood products stored for 30 days at BDU of IRC of Banda Aceh City. Research benefits are knowing the risk of haemolysis in the processing of PRC blood products stored for 30 days at BDU IRC Banda Aceh City. This study used the cross-sectional method. The samples in this study amounted to 95 donor blood samples taken from blood bags with a shelf life of 30 days. Techniques sample sampling using a total sampling technique. Samples will be examined quantitatively with a value of the percentage of haemolysis of the blood sample. The samples test will be seen whether haemolysis occurs (0.8%) or not/non-haemolysis (0.8%) automatically using the HemoCue Plasma/Low tool. Of the 95 samples tested, 7.3% (7) of the samples were haemolyzed and 92.8% (88) samples did not have haemolysis. This study showed that the majority of samples did not have haemolysis with a percentage of 92.8% and those with haemolysis were only 7.3%. This shows that the quality of blood services at BDU of IRC of Banda Aceh City is still by Peraturan Menteri Kesehatan (PMK) or regulation of the minister of health standard No. 91 yr. 2015 with the percentage of samples that do not undergo haemolysis above 75%.